2008
DOI: 10.1021/jo800634r
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Rearrangement of Tertiary Allylic Alcohols Employing Oxoammonium Salts

Abstract: Practical and highly efficient methods for oxidative rearrangement of tertiary allylic alcohols to beta-substituted alpha,beta-unsaturated carbonyl compounds employing oxoammonium salts are described. The methods developed are applicable to acyclic substrates as well as medium membered ring substrates and macrocyclic substrates. The counteranion of the oxoammonium salt plays crucial roles on this oxidative rearrangement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 48 publications
3
87
0
Order By: Relevance
“…[85] Reactions occur via the adduct D, which is obtained by reaction of the tertiary alcohol with salt 10. Heterolysis of the C À O bond will lead to ion pair E, which then collapses to F. Intermediate F can eventually fragment to product 21 and the protonated hydroxylamine 11.…”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%
“…[85] Reactions occur via the adduct D, which is obtained by reaction of the tertiary alcohol with salt 10. Heterolysis of the C À O bond will lead to ion pair E, which then collapses to F. Intermediate F can eventually fragment to product 21 and the protonated hydroxylamine 11.…”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%
“…7 Unfortunately, all attempts to oxidatively rearrange allylic alcohol 3.12 to enone 3.13 were unsuccessful. The use of various Cr (VI) 8 reagents, hypervalent iodine reagents, 9 or Noxoammonium salts 10 was ineffective, and largely resulted in the recovery of starting material or decomposition. Attempts to isomerize the allylic alcohol without oxidation were also unsuccessful.…”
Section: And Ester Formationmentioning
confidence: 99%
“…In turn, 1.7 serves as the progenitor to many different alkaloid frameworks including the strychnos, mavacurine, and akuammiline varieties. 10 For example, the strychnos alkaloid preakuammicine (1.8) would arise from a cyclization between C2 and C16, whereas the mavacurine alkaloid pleiocarpamine (1.9) stems from a cyclization between N1 and C16. The akuammiline framework, on the other hand, derives from an intramolecular oxidative coupling between C7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26] They exhibit extremely high activities toward a wide range of alcohols, including structurally hindered secondary alcohols that TEMPO fails to efficiently oxidize. 20,21) A structure-activity comparison indicated that the steric congestion near the active center exerts a critical impact on catalytic efficiency.…”
mentioning
confidence: 99%